2016
DOI: 10.15421/011634
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological mechanisms of formation of non-chemical dependence through self-stimulation of positive emotiogenic areas of rats’ brains

Abstract: The aim of our research was to study the limbic-neocortical mechanisms of addictive behaviour in rats formed throughthe arousal of intense emotions on the model of self-stimulation reaction of the brain. We carried out investigations by conducting a chronic experiment on 15 nonlinear laboratory male rats weighing 250 to 320 grams, at the ages of 5 to 6 months. As a model of receiving positive emotions we used the behaviour of animals held in a Skinner box which was formed through self stimulation of the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Some authors showed (Murzin et al, 2015;Berchenko et al, 2016) that delta-activity and rhythm synchronization are prevalent in on electrocorticograms of juvenile and young rats. According to some studies (Chaus et al, 2008;Turic'ka et al, 2016), indicators of the power of the delta-rhythm of bioelectric activity of the cerebral cortex of control animals in percentages fluctuated within 73.2-87.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors showed (Murzin et al, 2015;Berchenko et al, 2016) that delta-activity and rhythm synchronization are prevalent in on electrocorticograms of juvenile and young rats. According to some studies (Chaus et al, 2008;Turic'ka et al, 2016), indicators of the power of the delta-rhythm of bioelectric activity of the cerebral cortex of control animals in percentages fluctuated within 73.2-87.6%.…”
Section: Discussionmentioning
confidence: 99%